The Development of Teacher Professionalism in Implementing Curriculum and Learning Management Towards Education 5.0 - Kuryani, Tutus; Timan, Agus (Universitas Negeri Malang, 2024)
The transformation of education through curriculum and learning management is a critical aspect of adapting to modern demands. Education transformation in response to the challenges posed by Industry 5.0 and Society 5.0 demands education transformation manifested to re-conceptualization of curricula and pedagogical practices. This study aimed to assess the professional development of teachers in implementing curriculum management towards Education 5.0. The study in this article applied systematic literature review (SLR) using Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) resulting in 225 articles (5 records included) were screened. The results showed that teacher professionalism is an essential factor in improving educational systems and ensuring high-quality teaching. It is imperative to establish professional development through continuous professional development programs for teachers, advocating systemic changes that enhance teaching practices and foster collaborative learning environments to better meet the evolving needs of students.